TERMS OF ADDRESS IN ARABIC AT THE ARAB COMMUNITY IN MEDAN CITY AND THEIR INFLUENCES IN THE INDONESIAN LANGUAGE DEVELOPMENT - Suri, Nur Sukma; Mascahaya, Mascahaya; Ritonga, Farida Hanum (IMLA (Arabic Teacher and Lecturer Association of Indonesia), 2020)
Arabic language influences Indonesian vocabulary in term of borrowing words from Arabic, thus adding vocabulary to Indonesian. Vocabulary address form in Arabic are: ummi, abi, jid, jiddah, khale, khalati, amme, ammeh, ane, ente, antum, ustadz, ustadzah, mu'allimah, habib, bin, binti, akhi, ukhti, buya and the other. This is a field research and literature study aimed to explore terms of address in Arabic at the Arab community in Medan city and their influence in the Indonesian language development in Medan. This is a descriptive study using a qualitative approach that reveals facts, circumstances, phenomena which occur. This research conducted and presented data as it was, especially regarding to addressing terms used in the Arab Community city of Medan.